-(-5v+y)+6(2y-5v)=

Simple and best practice solution for -(-5v+y)+6(2y-5v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-5v+y)+6(2y-5v)= equation:


Simplifying
-1(-5v + y) + 6(2y + -5v) = 0
(-5v * -1 + y * -1) + 6(2y + -5v) = 0
(5v + -1y) + 6(2y + -5v) = 0

Reorder the terms:
5v + -1y + 6(-5v + 2y) = 0
5v + -1y + (-5v * 6 + 2y * 6) = 0
5v + -1y + (-30v + 12y) = 0

Reorder the terms:
5v + -30v + -1y + 12y = 0

Combine like terms: 5v + -30v = -25v
-25v + -1y + 12y = 0

Combine like terms: -1y + 12y = 11y
-25v + 11y = 0

Solving
-25v + 11y = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-11y' to each side of the equation.
-25v + 11y + -11y = 0 + -11y

Combine like terms: 11y + -11y = 0
-25v + 0 = 0 + -11y
-25v = 0 + -11y
Remove the zero:
-25v = -11y

Divide each side by '-25'.
v = 0.44y

Simplifying
v = 0.44y

See similar equations:

| 3*-5y=15 | | 12x+18y=1 | | y=-x^2+4x+45 | | 3*0-5y=15 | | 2x-1/2x=0 | | 10=2(y-3)-6y | | 2.5x-7.5=x | | x-2*-2=6 | | -40+6p+p^2= | | 2xyz-10xy-49y= | | 3(x-2)+12=6x+5-3x | | 3x^2-22x-7=0 | | -75727.82/87.08= | | 39.76-(6.46)+(53.78)= | | 41.4-8.8(-75.2)(-114.5)+2.3= | | -1530-(-573)= | | 10+5x=5y | | 4-(-0.25)-0.5= | | c^2-17c+72= | | 0=3x^4-10x^3+3x^2+12x-4 | | 9-8-2(7-5)= | | 17x-.57=1.43x-.077x-3.524 | | .17x-.57=1.43x-.0077x-3.524 | | ((5n^2)-14n)(n^2)=0 | | x+(x+7)+(x+9)=180 | | 4x-10-6x+3=7-9x-9+2x | | ((5m^7n^6)/(10m^5))^4^ | | H=-4.9t^2+15t | | 3(x^2-9)=2x | | 16-4ln(3)x=2 | | .10+4x=5(x-6)+33 | | log(7)x+log(7)(6x-1)=1 |

Equations solver categories